Transformasi Pendidikan Islam Di Jawa Pada Masa Kerajaan Demak, Pajang, Mataram, Cirebon, Dan Banten - Harnita Harnita; Ersa Putri; Fadel Muhammad; Idrus L. (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2026)
The transformation of Islamic education in Java during the Demak, Pajang, Mataram, Cirebon, and Banten kingdoms demonstrated a dynamic development process in line with the spread of Islam and changes in the socio-political structure of Javanese society. This study aims to analyze the transformation of Islamic education, the role of the kingdom and ulama in its development, and the characteristics of the educational system in each Islamic kingdom in Java. The study employed a literature study method by reviewing various sources, including books, scientific articles, journals, and relevant historical documents. The results show that Islamic education evolved from simple teachings in mosques and surau (prayer rooms) to more structured Islamic boarding schools (pesantren). During the Demak period, Islamic education focused on da'wah (Islamic preaching) and the formation of the foundations of Islamic teachings through the role of the Wali Songo (Nahdlatul Ulama). The Pajang period marked the consolidation of pesantren-based education. During the Mataram era, Islamic education was integrated with palace culture and traditions, forming a distinctive Javanese-Islamic character. Meanwhile, Cirebon and Banten developed as centers of Islamic education based on trade and international ulama networks. This transformation demonstrates that Islamic education functions not only as a medium for transmitting religious knowledge but also as a social, political, and cultural instrument in shaping Islamic society in Java. In conclusion, the development of Islamic education during the Islamic kingdoms in Java contributed significantly to the formation of scholarly traditions, Islamic boarding school culture, and the identity of the Indonesian Muslim community, which persists to this day.